Long-term quality of life in children with complex needs undergoing cochlear implantation. (September 2020) - Fraser, Lyndsay; Johnston, Susan; Wardrop, Peter; Shanks, Mary; Allen, Agnes
Abstract: Objectives: An estimated 30–40% of children undergoing cochlear implantation (CI) have additional disabilities and traditional outcome measures are often not reliable or appropriate. Few studies have evaluated long-term quality of life (Qol) in this group. Our aim was to assess long term QoL of children implanted with complex needs against a cohort of children implanted without. We also compared both groups for secondary outcome measures such as parental opinion, complications and hours of device wear. Methods: A retrospective casenote review of all children undergoing assessment between 2005 and 2010 was undertaken. Children with complex needs were identified using the Scottish Complex Needs Group Criteria (ISD 2006). Quality of life was measured using the GCBI (Glasgow Children's Benefit Inventory) which is a validated questionnaire suitable for the retrospective assessment of health-related QoL following paediatric surgical interventions. It consists of a 200-point scale which ranges from −100 (maximal harm) to +100 (maximal benefit) and can be analysed in four QoL subdomains (health, vitality, physical, learning). Parents were also asked to complete a simple questionnaire asking if they would recommend CI to other families and whether they would wish their child to undergo CI if given the option again. Results: 174 children were implanted and 17 (10%) were found to have complex needs. Follow-up ranged from 4 to 9 years. Total GCBI scores were similarly high between groups but significantly higher scores were found in the emotion (p = 0.05) and learning domains (p = 0.03) in the complex needs group. Linear regression analysis was used to show that total GCBI score was not influenced by the number of categories of impairment (R 2  = 0.0123) in the complex needs group. All parents of children with complex needs said that they would proceed with implantation again or recommend to a friend. The complication rate in the complex needs group was higher (29 vs 15%), with device failure being particularly more common. Data-logging was consistent between both groups. A higher rate of development of significant other health issues that could affect outcome was found in the complex needs group (35% vs 8%). Conclusions: Our study suggests that children with complex needs have comparable long-term QoL scores to those without and seem to particularly benefit in the domains of learning and emotion. Complications are higher in this group and there remains an increased risk of further development of medical conditions following early implantation, which may influence progress.